Bank Debit Taxes in Latin America : An Analysis of Recent Trends - Coelho, Isaias; Ebrill, Liam.; Perry, Victoria (Washington, D.C. : International Monetary Fund, 2001)
Six Latin American countries have levied taxes on withdrawals from bank accounts, which have been viewed as a convenient tax handle during a difficult fiscal period. The paper reviews the arguments for and against this type of taxation, describes the taxes, and surveys their revenue performance and economic impact. It concludes that the recently implemented taxes have been successful in raising revenue in the short term, but that adverse allocational impacts have likely been significant. The tax may work better in times of fiscal crisis, when financial intermediation is deep, and when the tax rate is modest.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet